Does reputation matter for firm risk in developing country? - Brahmana, Rayenda Khresna; Hui-Wei, You; Evan, Lau (John Wiley & Sons, Inc., 2020)
This research examines the effect of corporate reputation for firm risk in a developing country for a sample of 256 Indonesia firms for the period 2011–2015. Using two-step generalized method of moments approach, this research documents five important findings: (a) firm with higher reputation exhibits lower total risk (stock return volatility) and lower tail risk, yet, no significant effect on default risk; (b) Firms with high leverage use reputation effect for less total risk, tail risk, and default risk; (c) Firms with low leverage only enjoy the reputation effect on less total risk, but no reputation effect on tail risk and default risk; (d) Firms with high profitability utilize reputation to reduce the tail risk and default risk; and (f ) firm with low profitability has less tail risk when their reputation is high. This evidence contributes to the literature by uncovering important and previously unidentified determinants of risk, namely, reputation. It offers an insight to stakeholders that reputation does matter.